2021
DOI: 10.3389/fdgth.2021.722186
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Hearing Aid Usage Patterns and Smartphone Connectivity

Abstract: Data for monitoring individual hearing aid usage has historically been limited to retrospective questionnaires or data logged intrinsically in the hearing aid cumulatively over time (e. g., days or more). This limits the investigation of longitudinal interactions between hearing aid use and environmental or behavioral factors. Recently it has become possible to analyze remotely logged hearing aid data from in-market and smartphone compatible hearing aids. This can provide access to novel insights about individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…Sound levels found in this study were overall higher and more varied than those found by Christensen et al (2021a,b). Using a similar method, these authors found a grand median SPL among 98 hearing aid users of 54.42 dB (SD = 6.68 dB).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Sound levels found in this study were overall higher and more varied than those found by Christensen et al (2021a,b). Using a similar method, these authors found a grand median SPL among 98 hearing aid users of 54.42 dB (SD = 6.68 dB).…”
Section: Discussioncontrasting
confidence: 57%
“…Because the devices were programmed to collect sound levels throughout the day, we believe these data are reasonably representative. However, we do now know if comparing the overall mean sound level is the best indicator of differences in auditory environments between groups, as there could be fluctuations in sound level throughout the day (Christensen et al 2021a,b). In future work, additional analysis techniques could be implemented to identify how patterns of auditory environments encountered over time differ between groups.…”
Section: Discussionmentioning
confidence: 99%
“…When measuring performance in noise, an adaptive SNR procedure was used. The effect of noise could be more extensively studied by evaluating ASR by determining the Word Recognition Score (the convention in the field of audiology) or the Word Error Rate (the convention in the field of ASR research) on several fixed SNR levels (e.g.,−5, 0, +5 and +10 dB SNR) that correspond to realistic listening conditions for people using a hearing aid ( 36 ). For ecological valid measures, the effect of different fluctuating noise maskers should be considered ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its putative importance and comparatively easy influenceability, research at the junction of HA use time and associated psychological influences in adults is sparse [ 18 ]. The majority of studies focuses on audiological predictors of HA use [ 19 ] oand psychological influences on HL that are either unsusceptible to HA use [ 20 ] or improve following hearing amplification [ 21 ]. “Previously identified psychological predictors of HA nonuse include ‘perceived stigma’, ‘cosmetic concerns’, ‘disappointment with HA’, ‘oversold expectations’, or ‘family pressure to get HAs’ [ 22 ].…”
Section: Introductionmentioning
confidence: 99%